2022
DOI: 10.52965/001c.57622
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low bone mineral density at axial sites and fracture risk in Bulgarian population

Abstract: Background Osteoporosis is a common chronic disease characterized by low bone mineral density (BMD) and microarchitectural deterioration of the bone, which are associated with increased risk of fragility fractures. Currently the most popular tool is the fracture risk assessment model FRAX to calculate the 10-year probability of major osteoporotic fractures (MOF) and hip fractures (HF). Objective To investigate the prevalence of low BMD at axial sites and fracture risk in Bulgarian population. Methods We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Further, some studies showed that older people in the United States had a lower femoral neck bone mass density in the 2005-2006 period than in 1988-1994, indicating that they were at high risk for hip fractures [38]. A recent study in Bulgaria reported similar results [39]. In addition, some authors suggested that changes in trends correlated with changes in environmental and/or intrinsic factors, such as poverty, ethnicity, rurality, changes in body mass index, osteoporosis medication, the plasma level of vitamin D, sun exposure, calcium intake, nutritional status, and physical activity [5,[22][23][24].…”
Section: Discussionmentioning
confidence: 84%
“…Further, some studies showed that older people in the United States had a lower femoral neck bone mass density in the 2005-2006 period than in 1988-1994, indicating that they were at high risk for hip fractures [38]. A recent study in Bulgaria reported similar results [39]. In addition, some authors suggested that changes in trends correlated with changes in environmental and/or intrinsic factors, such as poverty, ethnicity, rurality, changes in body mass index, osteoporosis medication, the plasma level of vitamin D, sun exposure, calcium intake, nutritional status, and physical activity [5,[22][23][24].…”
Section: Discussionmentioning
confidence: 84%
“…Different surveys and interviews are done to analyze the main causing factors which can only be done with the help of patients and their medical history. According to Kirilova et al, 4 the most recommended and reliable way to assess osteoporosis is the analysis of bone mineral density with dual‐energy x‐ray absorptiometry. This is a cost‐effective and moderate method but it involves an adequate amount of radiation exposure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Osteoporosis is often neglected or slightly considered around the globe but this disease has a great negative impact on the health of humans because it can cause disability and in severe cases, it can also cause mortality. 3 Mostly in older people, this bone disease is increasing rapidly 4 but there are no necessary preventive measures are taken which is causing higher rates of bone fractures and other vertebral diseases. The expansion rate of osteoporosis 4 and causing fractures is increasing in more than 50‐year‐old individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained by the immobilization and the poor quality of life of patients with accompanying pHOA. (c) BMD population trials in Bulgaria among women [42] and men [43]. For women above 50 years of age, the results showed osteoporosis in 16.8%, osteopenia in 45.5%, and normal BMD in 37.7% [42].…”
mentioning
confidence: 99%